Relationship between body condition score, blood metabolites and oxidative stress in transition period and reproductive performance of dairy cows - ÇOLAKOĞLU, H. E.; YAZLIK, M. O.; KAYA, U.; KURT, S.; BAYRAMOĞLU, R.; VURAL, R.; KÜPLÜLÜ, Ş. (Journal of the Hellenic Veterinary Medical Society, 2020)
The aim of the current study was to investigate the relationship between prepartum body condition score (BCS), blood metabolites (Glucose, beta-hydroxybutyrate; BHB), oxidative stress (Malondialdehyde; MDA, Glutathione peroxidase; GSH-Px) in transition period and some reproductive parameters in Holstein dairy cows. Fifty cows were divided into two groups [low-BCS = 2.75-3.0 (n=25); adequate-BCS = 3.25-3.75 (n=25)] according to BCS on the 21st day before expected calving. BCS was also recorded at 0 and +21 days after calving. Blood samples collected at -21, 0 and +21 days from calving for MDA and GSH-Px analysis as well as at -21, +14 and +21 days of postpartum for glucose and BHB. Data on reproductive parameters obtained from farm records were also collected. MDA concentrations were higher in group of low-BCS compared to group of adequate-BCS at -21 and 0 d related to calving (p<0.05). GSH-Px activity was lower in group of low-BCS than adequate one during the transition period (p<0.05). Low-BCS group also showed higher concentrations of BHB at +14 and +21 days after calving. During the transition period, low-BCS group had lower glucose concentrations compared to adequate one (p<0.05). Adequate-BCS group of cows showed shorter intervals of calving to first estrus (p<0.01) and calving to conception (p<0.01). In conclusion, cows with lower BCS at the prepartum period had worse metabolic and oxidative balance during the transition period. This situation also was associated with worse reproductive performance in cows.